Rancang Bangun Aplikasi Presensi Siswa Berbasis QR Code pada SMK Swasta Bina Satria Medan - Nugraha, Rendy Editya; Soeheri, Soeheri (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2025)
Student attendance is a routine activity in schools that serves to monitor students’ presence and acts as an indicator of discipline. At SMK Swasta Bina Satria Medan, the attendance process is still carried out manually using paper-based attendance lists, which is time-consuming, prone to fraud, and at risk of data loss. To address these issues, a technology-based attendance system that is fast, accurate, and integrated is required. This study aims to design and develop a student attendance application based on QR code technology, which can be used by subject teachers through Android devices. Each student has a personal QR code displayed through a dedicated Android application for students. Teachers scan the QR code using the Android application to automatically record attendance into the database. The system is developed using Java with MySQL as the database. The test results show that the application can perform attendance quickly and accurately, minimize recording errors, and reduce the potential for fraud. Attendance data is stored digitally and can be easily recapped according to the desired period. With this application, the attendance administration process at SMK Swasta Bina Satria Medan becomes more efficient and practical and supports digital transformation in the school environment.